Pemikiran Pendidikan Islam Imam Al-Ghazali dan Relevansinya Terhadap Pendidikan Modern - Dian Aura Sabillah Simamora; Abdusima Nasution; Nursri Hayati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to examine the Islamic educational thought of Imam Al-Ghazali and analyze its relevance to modern education. This research employs a qualitative approach with a library research method. The primary data are derived from Al-Ghazali’s classical works, while secondary data are obtained from various scientific journals and supporting literature. Data collection is conducted through documentation techniques, and data analysis uses a descriptive-analytical method. The results indicate that Al-Ghazali’s educational concept emphasizes the holistic development of human beings, encompassing intellectual, spiritual, and moral aspects. The purpose of education is not merely to achieve academic success but also to purify the soul and cultivate noble character. In addition, Al-Ghazali highlights the importance of intention in seeking knowledge, the role of teachers as moral exemplars, and the classification of knowledge based on individual and social needs. Al-Ghazali’s educational thought remains highly relevant to modern education, particularly in addressing issues such as moral crises, ethical degradation, and the dominance of materialistic approaches. The integration of cognitive, affective, and spiritual aspects proposed by Al-Ghazali can serve as a foundation for developing a more humanistic and character-oriented educational system.